Pendekatan individual terhadap slow learner: perspektif bimbingan dan konseling Islam - Ranita; Muhammad Guruh Nuary (Ikatan Konselor Indonesia (IKI))
This research discusses about slow learner that has an obstacle in obtaining information for the students due to differentiate in learning styles and learning materials as well as the arrest of one individual to the others. This research presents the data from the A (8) who studies at SDN 3 Ambulu, Losari, Cirebon. The researchers use Research and Development with quantitative single object approach which is supported by experimental method that the researchers gave the treatment to enhance the abilities of A (8) such as read, write and count using Audio Lingual Method (ALM) for learning with instruments that provides the development from A in this treatment. The treatment for A (8) was success to be implemented for A (8). So, in this research the researchers will only deliver the treatment that help A (8) to enhance reading, writing and counting abilities that is relevance with A (8) as a Slow Learner in the guidance and counseling perspective.